2011
DOI: 10.1253/circj.cj-10-0600
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention With Rosuvastatin Decreases the Lipid Components of the Plaque in Acute Coronary Syndrome - Analysis Using Integrated Backscatter IVUS (ELAN Study) -

Abstract: Background: It has recently become possible to analyze coronary plaque characteristics by using integrated backscatter intravascular ultrasound (IB-IVUS). The aim of this study was to use this modality to evaluate the impact of early intervention with rosuvastatin on both the volume and tissue characteristics of non-culprit plaques in acute coronary syndrome (ACS). Methods and Results:Patients with ACS underwent IB-IVUS after percutaneous coronary intervention procedure and were administered rosuvastatin. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 31 publications
3
19
0
2
Order By: Relevance
“…Recent studies conducted in Japan have suggested the L/H ratio as a predictor of clinical outcomes in patients after percutaneous coronary intervention, 33 and in the general population. 34 Functional improvement observed in the present study corresponded well with the recent finding by Otagiri et al, 35 who found beneficial vascular structural changes, including a significant reduction of lipid components of the coronary plaque, in Japanese patients with ACS following early administration of low-dose rosuvastatin (2.5 mg/day up to 5 mg/day) for 6 months. In Protocol 2, all patients who had been switched from usual-dose fluvastatin to rosuvastatin attained the target LDL-C level at 12 months after the switch.…”
Section: Other Drugssupporting
confidence: 92%
“…Recent studies conducted in Japan have suggested the L/H ratio as a predictor of clinical outcomes in patients after percutaneous coronary intervention, 33 and in the general population. 34 Functional improvement observed in the present study corresponded well with the recent finding by Otagiri et al, 35 who found beneficial vascular structural changes, including a significant reduction of lipid components of the coronary plaque, in Japanese patients with ACS following early administration of low-dose rosuvastatin (2.5 mg/day up to 5 mg/day) for 6 months. In Protocol 2, all patients who had been switched from usual-dose fluvastatin to rosuvastatin attained the target LDL-C level at 12 months after the switch.…”
Section: Other Drugssupporting
confidence: 92%
“…Another pivotal finding emerging from Tian's meta-analysis is that statin-induced plaque regression was twofold greater in ACS as compared to SA patients [61] in agreement with previous reports [31,58]. This discrepancy is likely due to the different plaque composition, because the plaques of ACS patients have larger necrotic lipid core, the main target of statin treatment [53,54,56,57]. Furthermore, the IVUS-assessed plaque regression has been associated with decrease in serum levels of hs-CRP [58,62], ApoB and MMP-9, as well as to increased levels of TIMP-1 [55].…”
Section: Statin-associated Benefits In Patients Admitted For Acs Undesupporting
confidence: 81%
“…There was also a reduction in CK-MB, cTnI and hs-CRP compared to placebo group (P < 0Á01) (P < 0Á0001), at 6-month follow-up [50]. Other studies reported in Table 4, mostly designed by Japanese research groups, provided similar results further supporting the effectiveness of statin treatment in promoting plaque stabilization [51][52][53][54][55][56][57][58][59][60]. Both randomized clinical trial and prospective interventional studies confirmed the improvement in plaque dimension and composition induced by high-dose and long-term statin therapy is strongly associated with decreased circulating LDL [50,52,54,56,59].…”
Section: Statin-associated Benefits In Patients Admitted For Acs Undementioning
confidence: 64%
“…18) Furthermore, the ELAN study showed that 2.5-5 mg/day of rosuvastatin caused LDL-C levels to decrease by 38% and plaque volumes to regress by 18%. 19) Similarly, we showed that atorvastatin and rosuvastatin caused LDL-C levels to decrease by 41.2% and 38.8%, respectively. Although both statins were taken in low doses by patients, the LDL-reducing effects observed by us were similar to those induced by higher doses.…”
Section: Discussionmentioning
confidence: 58%